2011
DOI: 10.1159/000328255
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Dementia among Elderly People Living in Cotonou, an Urban Area of Benin (West Africa)

Abstract: Background/Aims: The population of Benin is, like those of most developing countries, aging; dementia is therefore a major concern. Our goal was to estimate the prevalence of dementia in an elderly population living in urban Benin. Methods: In a cross-sectional community-based study, people aged 65 years and above were screened using the Community Screening Interview for Dementia and the Five-Word Test. Results: The prevalence of dementia was 3.7% (95% CI 2.6–4.8) overall. The figure increased with age and was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 59 publications
3
48
2
1
Order By: Relevance
“…When provided, age at clinical diagnosis of disease ranged from 80.7 to 83.8 years. Alzheimer disease was the most common form of the disease, representing 57.4 to 89.4 % of all cases [30-32,34,42,45,55,56,63,71,74], followed by vascular dementia 5.7 to 31.0% of cases [30,31,45,56,74]. Four publications in Nigeria provided incidence data for dementia ranging from 8.7 to 21.8 cases per 1000 per year [35,51-53].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When provided, age at clinical diagnosis of disease ranged from 80.7 to 83.8 years. Alzheimer disease was the most common form of the disease, representing 57.4 to 89.4 % of all cases [30-32,34,42,45,55,56,63,71,74], followed by vascular dementia 5.7 to 31.0% of cases [30,31,45,56,74]. Four publications in Nigeria provided incidence data for dementia ranging from 8.7 to 21.8 cases per 1000 per year [35,51-53].…”
Section: Resultsmentioning
confidence: 99%
“…The most commonly used tool for dementia screening was the Community Screening Interview for Dementia (CSID) questionnaire applied in 20 publications [32,34,36,37,41-43,45-47,49,50,54,56,65,70]. The diagnosis of dementia mainly relied on the DSM-III-R/DSM-IV and ICD-10 classification [30,32,34-37,40,42-46,52-54,63,70].…”
Section: Resultsmentioning
confidence: 99%
“…Prevalence was similarly low in rural Benin (2.4% age-standardized for age 65+ and 2.0% for age 60+ similarly estimated) (38). The prevalence in urban Benin was higher (4.3% and 3.5%) (40) and that recorded in cities in the Central African Republic (10.1% and 8.2%) and the Republic of the Congo (7.2% and 6.0%) was substantially higher (39).…”
Section: Dementia Subtypesmentioning
confidence: 79%
“…Subsequent studies from francophone countries in western and central Africa (38)(39)(40), and one further study from northern Nigeria (41) suggest a more variable prevalence, higher in urban than in rural sites, and higher in central compared with western Africa. The Nigerian study recorded a low prevalence that is consistent with findings from the earlier USA / Nigeria study (2.4% for those aged 65 and over, age-stan- suggested that the true prevalence at baseline was likely to be much closer to the 7.5% recorded for 10 / 66 dementia than the 0.9% prevalence according to DSM-IV criteria (20).…”
Section: Discussion -Prevalence Of Dementiamentioning
confidence: 99%
“…They initiated and developed long-term research and action programs for dementia in several Central African countries, despite periodic bouts of civil unrest there [2,3,4]. They also identified a tool for determining the accurate age of dementia subjects - an extremely important issue in dementia research [5] - as well as certain psychosocial factors important in the survival of demented subjects [2].…”
Section: Dementiamentioning
confidence: 99%